Rescue, ecology and conservation of a rediscovered island endemic fern (Anogramma ascensionis): ex situ methodologies and a road map for species reintroduction and habitat restoration. (23rd January 2014) - Baker, Katie; Lambdon, Phil; Jones, Edward; Pellicer, Jaume; Stroud, Stedson; Renshaw, Olivia; Niissalo, Matti; Corcoran, Marcella; Clubbe, Colin; Sarasan, Viswambharan
<x xml:space="preserve">Abstract</x> Last seen in 1958, the Ascension Island endemic fern, Anogramma ascensionis, was listed as extinct on the 2003 IUCN Red List. However, a 2009 survey rediscovered four plants on Green Mountain. Spores were collected and cultured in vitro at the Royal Botanic Gardens, Kew, where a living collection of thousands of gametophytes and hundreds of sporophytes has been developed. To gain further insights into the biology of this species and the potential implications of in vitro multiplication for conservation purposes, samples were characterized from the karyological point of view. Chromosome analysis of root tips has confirmed that the species is tetraploid, and flow cytometry assessments have revealed that haploid gametophytes produce diploid sporophytes, which confirms natural fertilization. In addition, an rbcL sequence from A. ascensionis has been generated and compared with those published for other Anogramma spp., suggesting a close relationship with A. chaerophylla from Brazil. Further surveys of Green Mountain have reported the presence of 40 A. ascensionis sporophytes in total. Vegetation community analyses have suggested that the present population may be confined to suboptimal habitats. We therefore propose that, prior to the dramatic transformation of the vegetation on the island as a result of the invasion of alien species (particularly Adiantum spp.), A. ascensionis may have flourished in more humid and shaded parts of the mountain. A multidisciplinary approach involving in vitro culture, invasive species clearance and controlled translocation is discussed as the future roadmap for the conservation of this critically endangered fern. Our experiences have also highlighted lessons more broadly applicable to the conservation of extremely rare species elsewhere in the world, especially on remote island systems. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 174, 461–477.